Detection of Quinolone Resistance qnr genes and its Association with Carbapenemase Genes in qnr Positive Enterobacteriaceae in a Tertiary Hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2025)
Background: Multidrug resistance in Enterobacteriaceae is dramatically increasing worldwide day by day.Objective: The purpose of the present study was to detect the prevalence of quinolone resistance qnr genes and its association with carbapenemase genes in qnr positive Enterobacteriaceae.Methodology: This cross-sectional study was conducted from January 2015 to December 2015 at Dhaka Medical college Hospital, Bangladesh. A total of 270 Enterobacteriaceae were collected from inpatient and outpatient departments of DMCH irrespective of age, sex and antibiotic intake analyzed for antibiotic susceptibility. The qnr determinant screening among ciprofloxacin resistant strains were conducted using PCR amplification. Searching of carbapenemase genes in qnr positive Enterobacteriaceae were conducted also by using PCR.Results: The qnr gene was detected in 141 (62.67%) of the 225 quinolone resistant isolates by using PCR. Highest proportion of qnrS were detected followed by qnrB and qnrA from quinolone resistant strains. qnrB genes were co-existed with NDM-1, VIM, IMP and KPC genes. qnrS genes were also associated with NDM-1, VIM, IMP and KPC genes. Antimicrobial-resistance rates of Enterobacteriaceae to ciprofloxacin was 83.33%.Conclusion: The qnr genes were highly prevalent in Enterobacteriaceae. They were closely associated with carbapenemase genes.Bangladesh Journal of Medical Microbiology, July 2024;18(2):93-100